Novel Internet of Things (IoT) for controlling indoor temperature via Gaussian type-2 fuzzy logic. (4th March 2021) - Jana, Dipak Kumar; Basu, Sweta
ABSTRACT: Due to the rapid development in information and communication technologies, the Internet of Things (IoT) is a popular term in the areas of research. In this paper, we propose Gaussian type 2 fuzzy logic controller (GT2FLC) and applied to IoTs to manage indoor temperature concerning the outdoor ambient circumstances. Three input parameters have been controlled by GT2FLC for the purpose of saving energy and to place a more relaxing atmosphere for the users. The improvement of indoor temperature relies on various factors like the various combinations of outdoor temperature and humidity. The validity of the proposed model is made with the help of statistical analysis and multiple linear regressions. The simulation results revealed that the proposed system was more dependable and approachable to manage indoor temperature as compared to the offline monitoring system used outdoor ambient situations.